Platelet aggregation, mean platelet volume and plasma fibrinogen as risk factors for acute myocardial infarction - Yadav, Geeta; Kushwaha, Rashmi; Ali, Wahid; Singh, Uma S.; Kumar, Ashutosh; Chandra, Sharad; Awasthi, Ashish; Mishra, Prabhaker (International Journal of Research in Medical Sciences, 2018)
Background: The Aim of this study was to assess the role of platelet aggregation, mean platelet volume (MPV) and plasma fibrinogen levels in the pathogenesis of acute myocardial infarction (AMI). Methods: A prospective case control study was conducted on 30 cases of AMI and 30 normal healthy age and sex matched controls. The cases and controls were investigated for platelet aggregation studies (done in platelet rich plasma (PRP) using light transmission chrono-log optical aggregometer), MPV (measured by automated cell counter) and plasma fibrinogen levels (estimated by Clauss method). Results: The mean platelet aggregation (%) in cases AMI was 57.61±11.91 which was significantly higher compared with 35.00±10.40 for healthy controls (p<0.001). Using Receiver Operating Characteristic (ROC) analysis, most patients of AMI had a platelet aggregability of ≥49% on optical aggregometry (sensitivity = 83.3 % and specificity = 93.7%). The MPV (fL) in cases of AMI was 8.04±0.39 which was significantly larger when compared with 7.67±0.43 for controls (p= 0.001). The mean plasma fibrinogen concentration in cases of AMI was 383.1±48.3mg/dl which was significantly higher when compared with 271.33±57.7mg/dl for healthy controls (p<0.001). Conclusions: Platelet hyperaggregability, elevated MPV and plasma fibrinogen levels are found in patients with AMI and contribute significantly to risk of developing coronary thrombosis. These variables should be considered as additional screening tools to identify individuals at increased risk of developing AMI.